THE LANGUAGE INSTINCT (Steven Pinker vs Noam Chomsky) - Nur Cahaya Sihombing (English Lecturers and Teachers Association (ELTA), 2022)
Language is a communication tool used in daily interaction. Language used to convey meaning to someone with easy word order understandable. Therefore, in order to convey the meaning clearly, use of the correct language is very important. This paper examines Steve Pinker’s arguments for the existence of a language instinct encoded in the genes of human beings as an explanation for the human language capacity. The analysis covers Pinker’s own arguments as well as those by Chomsky and by other authors in the 1990s. Argumen of Steven Pinker language is first and foremost a product of our biological make-up as a species. Pinker does not mean to deny the influence of culture on language, but means that language grows out of the